(untitled) (Innovation in Woodworking Industry and Engineering design, 2026)
The results for the defining of the quantity of the intake substance (intake – P), swelling - shrinkage – the volume anti-swelling effect – ASEv, coefficient of effectivity – Kasev of the treated with conservative means beech timber (Fagus silvatica L.) and Macedonia pine (Pinus peuce Gris.) have been given. The processing of the sample bodies has been carried out in concordance with requirements of the active standards. As conservative means are used impregnator and finish – impregnator, offered by the Italian firm „Atria“. The results from the research could be used as recommendations in the furniture production, wood assembled houses and constructions in the special productions, as well as from laboratories for testing timber and timber materials, and for preventive control of the quality of the produced timber products.